Urgensi Tulisan Tangan Huruf Sambung bagi Pembelajaran Bahasa dan Identitas Nasional - Makhali Makhali; Daroe Iswatiningsih; Mochammady El Akbar (ENGGANG: Jurnal Pendidikan, Bahasa, Sastra, Seni, dan Budaya, 2026)
Cursive handwriting is one of the fundamental skills in Indonesian language learning at the elementary school level and plays an important role in students’ cognitive, motor, and affective development. However, over the past few decades, the practice of teaching cursive handwriting has gradually been marginalized due to the dominance of digital technology and shifts in educational paradigms. This article aims to comprehensively examine the urgency of cursive handwriting for elementary school students, particularly in the context of Indonesian language learning and the formation of national identity. This study employs a qualitative approach using a literature review method, analyzing various research findings published over the last five years. The results indicate that cursive handwriting contributes positively to the improvement of literacy skills, concentration, fine motor coordination, as well as the development of students’ character and learning discipline. Furthermore, handwriting, including cursive writing, holds symbolic value as part of cultural heritage and national identity that should be preserved amid the ongoing digitalization of education. Therefore, cursive handwriting instruction is not only pedagogically relevant but also strategically important in fostering character development and national identity from an early age.